Pengaruh Kepemimpinan Autentik dan Budaya Pelayanan Terhadap Kinerja Karyawan Fox Lite Hotel Samarinda - Regita Adelia; Tetra Hidayati; Melda Aulia Ramadhani (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to determine the effect of Authentic Leadership and Service Culture on Employee Performance at Fox Lite Hotel Samarinda. The number of samples in this study was 32 samples from a total population of 42 people. The data analysis method in this study used Partial Least Squares - Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4 software. The results of the study found that: (a) Authentic leadership has a positive but insignificant effect on employee performance. The results of hypothesis testing showed a path coefficient value of 0.234, a t-statistic of 1.904, and a p-value of 0.057. These values ​​indicate that the better the implementation of authentic leadership, the employee performance tends to increase, but the effect is not statistically strong enough. Thus, authentic leadership has not been the main factor that directly determines the high and low employee performance at FOX Lite Hotel Samarinda. Hypothesis 1 which states that authentic leadership has a positive and significant effect on employee performance is not proven and is rejected; and (b) Service culture has a positive and significant effect on employee performance. The results of the hypothesis testing showed a path coefficient of 0.663, a t-statistic of 5.586, and a p-value of 0.000. This means that the better the service culture implemented, the higher the employee performance. Service culture has been shown to be a dominant factor in shaping employee work behavior, particularly in providing friendly, responsive, polite, consistent, safe, and customer-satisfaction-oriented service. Hypothesis 2, which states that service culture has a positive and significant effect on employee performance, was proven and accepted.